How is patient care for multiple myeloma advancing?. Issue 6 (3rd June 2017) - Genadieva Stavric, Sonja; Bonello, Francesca; Bringhen, Sara; Boccadoro, Mario; Larocca, Alessandra
ABSTRACT: Introduction : Treatment of multiple myeloma has undergone profound changes in the past years thanks to the increased understanding of the biology of the disease and the new treatment options. New drugs and effective approaches are currently available for the treatment of multiple myeloma, including immunomodulatory agents, proteasome inhibitors and autologous stem cell transplantation. Areas covered : We have described the recent updated criteria to start treatment in multiple myeloma and summarized clinical data from major studies including most recent agents. Particularly, results with pomalidomide, carfilzomib, ixazomib, monoclonal antibodies such as elotuzumab, daratumumab, and checkpoint inhibitors have been reported. Both transplant and non-transplant settings have been covered. Expert commentary : Despite the successful improvement in overall survival and time to relapse, multiple myeloma still remains incurable. Therefore, there is still an unmet need for new treatment strategies with novel mechanisms of action, like monoclonal antibodies, novel immunomodulators, and novel proteasome inhibitors. Implementation of these novel drugs in rationally designed therapies with a good balance of efficacy and safety should be carefully considered in order to improve outcome.